BENTUK PERMINTAAN SOPAN DALAM BAHASA INGGRIS DAN BAHASA TALAUD (SUATU ANALISIS KONTRASTIF) - NUSA, BELSASAR RIAN; JANSEN, FRIEDA TH.; SENDUK, ARTER JODI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ This research is entitled â€œBentuk Permintaan Sopan dalam Bahasa Inggris dan Bahasa Talaud: Suatu Analisis Kontrastifâ€. The problem in this research is what are the forms of polite request in English and Talaud Language and, what are the similarities and difference between the two languages. The research question to be answered are how are the forms of polite request in English and Talaud Language and are there any similarities and differences in both languages. In terms of methodology, the writer used descriptive method and contrastive analysis. The whole data were collected by doing library and field research. The data of both languages were analyzed based on Ladoâ€™s (1971) theory. The result of this research shows that polite request in English and Talaud Language have some similaraties and differences. Both languages have polite forms. Besides, the differences in both languages are found in terms of structure, forms of sentences, distribution of verbs and personal pronouns which were used to address the hearers.Â Key Words: Polite Request, English and Talaud language, Contrastive Analysis. Â Â